Antibiotic screening of soil microrganisms isolated from remote village in Nanga Merit, Sarawak - Nurul Saiyidah, Abdul Rahim (Universiti Malaysia Sarawak, UNIMAS, 2010)
A study was conducted to isolate antibiotic-producing microorganisms from soil samples collected from a remote village in Nanga Merit Kapit, Sarawak. The soil was suspended and homogenized with phosphate buffer saline (PBS), and then was inoculated on potato dextrose agar (PDA) or nutrient agar (NA) by spread-plate method. Screening for the antibiotic-producing activity was accomplished through preliminary and secondary screening, by using agar overlay technique. These procedures were followed with antibiotic screening using disc diffusion test. Through preliminary screening, 16 bacterial and 8 fungi isolates that showed zone of inhibition were selected for secondary screening. After secondary screening, only six of the fungal isolates were selected for further experiment which involves extraction of antibiotic by methanol. This procedure involved drying of agar containing the selected isolates, followed by immersion of the dried agar in 10ml of absolute methanol. Antibiotic screening was then performed to screen antibiotic activity for the methanol extractions. Result showed that two types of fungal isolates, respectively coded as L10.1.F3 and L12.1.F1 carried the potential of producing antibiotic with strong zone of inhibition against test bacteria. Another four fungal isolates, coded as L11.2.F1, L11.2.F3, L11.2.F4, and L12.1.F1, only showed zone of inhibition on primary and secondary screening. Probabilities of having insufficient amount of antibiotic extracts may be the reason for these fungi to showed negative activity throughout the antibiotic screening. Even so, these finding suggest that soil from a remote village in Nanga Merit Kapit, Sarawak does contain with antibiotic-producing microorganisms. Isolation of novel strains of antibiotic-producing microorganisms from this location seems to be possible.